Extrapelvic Sciatic Nerve Endometriosis, the Role of Magnetic Resonance Imaging: Case Report and Systematic Review. Issue 6 (November 2019) - Lomoro, Pascal; Simonetti, Igino; Nanni, Annalisa; Cassone, Rosario; Di Pietto, Francesco; Vinci, Giorgia; Prevedoni, Maria Sole; Romano, Stefania; Sammarchi, Luigi
Abstract : Abstract: Endometriosis (EN) is a common gynecological condition characterized by the presence of functional endometrium located outside the uterine cavity. Sciatic nerve (SN) is rarely affected by EN. Magnetic resonance imaging allows a direct visualization of the spinal and SN, and it is the modality of choice for the study of SN involvement in extrapelvic EN. We report a case of an endometrioma located in the right SN with a systematic review of the literature.